The emerging role of 5-hydroxymethylcytosine in neurodegenerative diseases - Al-Mahdawi, Sahar; Virmouni, Sara Anjomani; Pook, Mark A. (Frontiers in Neuroscience, 2014)
DNA methylation primarily occurs within human cells as a 5-methylcytosine (5mC) modification of the cytosine bases in CpG dinucleotides. 5mC has proven to be an important epigenetic mark that is involved in the control of gene transcription for processes such as development and differentiation. However, recent studies have identified an alternative modification, 5-hydroxymethylcytosine (5hmC), which is formed by oxidation of 5mC by ten-eleven translocation (TET) enzymes. The overall levels of 5hmC in the mammalian genome are approximately 10% of 5mC levels, although higher levels have been detected in tissues of the central nervous system (CNS). The functions of 5hmC are not yet fully known, but evidence suggests that 5hmC may be both an intermediate product during the removal of 5mC by passive or active demethylation processes and also an epigenetic modification in its own right, regulating chromatin or transcriptional factors involved in processes such as neurodevelopment or environmental stress response. This review highlights our current understanding of the role that 5hmC plays in neurodegenerative diseases, including Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), fragile X-associated tremor/ataxia syndrome (FXTAS), Friedreich ataxia (FRDA), Huntington’s disease (HD), and Parkinson’s disease (PD).